Marfan Syndrome in Mid-Adulthood: A Detailed Case Report of a 47-Year-Old Female Patient - Yanamadala, Pavan Kumar; Akasapu, Madhuri; Bokka, Pradeepthi (Indian Journal of Pharmacy Practice)
Marfan syndrome is a hereditary connective tissue disorder with an autosomal dominant inheritance pattern, affecting the cardiovascular system, eyes, and musculoskeletal structure. While often diagnosed in childhood, late diagnosis, especially in middle-aged individuals, can complicate prognosis and treatment, leading to serious health issues. We present the case of a 47-year-old female with Marfan syndrome, who initially presented with complaints of chest pain, shortness of breath, and joint laxity. Physical examination revealed features characteristic of Marfan syndrome, including tall stature, arachnodactyly, and scoliosis. Echocardiography showed severe aortic root dilation and mitral valve prolapse, requiring immediate medical attention. Despite intensive treatment aimed at stabilizing her cardiovascular status, the patient’s condition progressively deteriorated. Complications, including acute aortic dissection, were noted, which ultimately led to her demise during treatment. This case underscores the challenges in diagnosing and treating Marfan syndrome, particularly regarding cardiovascular issues, when identified late. The patient’s delayed presentation led to more severe disease progression, limiting intervention effectiveness. To reduce the risk of life-threatening complications like aortic dissection, routine screening and early treatment for individuals with Marfan syndrome are crucial. The late diagnosis of Marfan syndrome in middle-aged individuals poses considerable risks, particularly concerning cardiovascular issues. This case underscores the critical necessity for early identification of the condition and emphasizes the importance of proactive cardiovascular surveillance, which can enhance patient outcomes and diminish the likelihood of mortality among those affected.
Keywords: Marfan syndrome; Aortic dissection; Cardiovascular complications; Late diagnosis; Connective tissue disorder; Mitral Valve Prolapse